Health assessment and the capability approach. Issue 1 (1st January 2019) - López Barreda, Rodrigo; Robertson-Preidler, Joelle; Bedregal García, Paula
ABSTRACT: Health has an important role in the achievement of a good quality of life. Many public policies intended to enhance individual and population health. Amartya Sen's Capability Approach (CA) offers a framework to assess well-being, as well as interventions seeking to increase it. There are, however, important practical challenges that must be faced before applying CA to concrete situations, such as health. One of these challenges is defining whether it is functioning or a capability that is the feature to be assessed. Moreover, some aspects of freedom that are relevant for CA are frequently neglected, such as agency. These aspects must be considered when performing a health assessment using the CA as a framework. A health assessment using the CA as a framework should include indicators based on the achieved dimension (health functioning), resources and conversion factors (health capability), and freedom to achieve (agency).